POLITICAL SIT-AT-HOME OR SOCIO-ECONOMIC SIT-AT-HOME IN SOUTHEAST, NIGERIA : A DEVELOPMENT CRISIS - Chibuzor Okoroafor, Ejike; Ogechi Osuji, Anthony; Uchenna Nwosu, Kingsley (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2023)
This paper is an exploratory reconnaissance on the sit-at-home order, its related issues, experiences and inherent challenges on the people of southeast, Nigeria. The sit-at-home commandment borne out of the separationist agitations of the Indigenous People of Biafra (IPOB), foists enormous fear and anxiety that keep some people indoors and others minimally mobile, and undermines life activities in the region. This two year old precarious Mondays sit-at-home issue, kidnappings, farmers/herdsmen clashes and other forms of criminality with their attendant fatal violence and conflicts constitute sources of severe psycho- social, political and economic challenges to the south-east inhabitants. This paper dwells on the issues surrounding the political and economic effects and implications of this non-state order on the security and economy of the southeast and national development. It interrogates the divergent and critical ramifications of the sit-at-home imbroglio, its potentials as precursor of self-inflicted economic setback within the historical context of marginalization and obscurity of a people characteristic of age long industrial enterprise. Moreover, good governance sensitive to the plights and interests of the southeasterners (Ndigbo), set-up of effective community based vigilante groups to counter the order, town-hall meetings for mass orientation on ills of the order were advocated as measures out of this national development crisis.